Keupayaan pihak berkuasa tempatan melaksanakan agenda pembangunan mampan alam sekitar: Kajian kes Majlis Daerah di Negeri Sembilan - Azman, Abdullah (2025)
The global sustainable development agenda has evolved through new phases since its inception. The Malaysian Government have committed to implementing the vision in line with the sustainable development agenda and entrusted local authorities to lead and drive this initiative. This study aimed to understand the issues and challenges faced by local authorities, specifically district councils, in implementing sustainable environmental development agendas within their jurisdictions. Internal and external stakeholders of district councils were involved in this qualitative study to achieve the study’s objectives. The qualitative case study was conducted in two districts in Negeri Sembilan, Malaysia, namely Kuala Pilah District Council and Jelebu District Council. Data were collected through face-to-face interviews with the President, Secretary, Director of Town Planning, Assistant Engineer, Head of the Tourism Unit, Account Assistant, labour and councillors for the district council, as well as officers from the district and state levels, through file reviews, document and website reviews, as well as field observations. The gathered data were then analyzed using framework-based thematic analysis, coding and categorizing into themes, and subsequently analysed using SWOT analysis to identify the councils’ strengths and weaknesses and recommend areas for improvement. The thematic analysis generated four main themes, including (1) strengths of the district councils, (2) weaknesses of the district council, and (3) opportunities for the district councils, and (4) threats to the district councils. The findings revealed that the district councils possessed inherent strengths that can be utilized for effective governance in sustainable environmental development, such as top management consciousness on environment, current initiatives being done by the district councils and commitment of the employees. However, the study highlighted the crucial role of external stakeholders (state government, as well as federal government through its ministries and agencies) in supporting the councils’ efforts. This study enriched the discussions on sustainable environmental development from a theoretical perspective. Practically, it provided insights to assist district councils and relevant authorities in strengthening their roles, especially in implementing sustainable development agendas, particularly in rural areas.